2020
DOI: 10.1186/s12866-020-01994-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering fungal community composition in natural habitat of Ophiocordyceps sinensis using high-throughput sequencing and culture-dependent approaches

Abstract: Background The fungal communities inhabiting natural Ophiocordyceps sinensis play critical ecological roles in alpine meadow ecosystem, contribute to infect host insect, influence the occurrence of O. sinensis, and are repertoire of potential novel metabolites discovery. However, a comprehensive understanding of fungal communities of O. sinensis remain elusive. Therefore, the present study aimed to unravel fungal communities of natural O. sinensis using combination of high-throughput sequencing and culture-dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Because of the relatively low abundance of fungi in the human gastrointestinal tract (comprising only 2% of the human gut microbiota) ( Anandakumar et al, 2019 ), little is known about their ability to influence human health and disease. With the advent of deep sequencing technologies, the composition and diversity of the fungal microbiota has been revealed, deepening and clarifying our understanding of the roles and mechanisms of intestinal fungi in host homeostasis ( Iliev and Leonardi, 2017 ; Scheffold et al, 2020 ; Zhang et al, 2020 ; Zou et al, 2020 ). Recent studies have unveiled the potential roles that fungi play in modulating host immune homeostasis and inflammatory disease ( Standaert-Vitse et al, 2006 ; Wheeler et al, 2016 ; Sokol et al, 2017 ; Yang et al, 2017 ; Cirstea et al, 2020 ; Huang et al, 2020 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively low abundance of fungi in the human gastrointestinal tract (comprising only 2% of the human gut microbiota) ( Anandakumar et al, 2019 ), little is known about their ability to influence human health and disease. With the advent of deep sequencing technologies, the composition and diversity of the fungal microbiota has been revealed, deepening and clarifying our understanding of the roles and mechanisms of intestinal fungi in host homeostasis ( Iliev and Leonardi, 2017 ; Scheffold et al, 2020 ; Zhang et al, 2020 ; Zou et al, 2020 ). Recent studies have unveiled the potential roles that fungi play in modulating host immune homeostasis and inflammatory disease ( Standaert-Vitse et al, 2006 ; Wheeler et al, 2016 ; Sokol et al, 2017 ; Yang et al, 2017 ; Cirstea et al, 2020 ; Huang et al, 2020 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preussia can produced glucosidases, phosphatases, cellulases, and IAA to promote plant development under stressful environmental conditions ( Kandar et al, 2018 , Toppo et al, 2022 ). Archaeorhizomyces can enhance plant bioactive components, improve stress resistance, and alleviate the occurrence of diseases ( Zhang et al, 2020 ). Furthermore, Mortierella , Fusicolla , and Stachybotrys play an essential role in reducing the effects of environmental stresses on plant growth, preventing disease and even promoting bioremediation ( Zhang et al, 2016 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, arbuscular mycorrhizal fungi (AMF) can assist plant to facilitate mineral and water uptake ( Debeljak et al, 2018 ; Begum et al, 2019 ). Archaeorhizomyces enhance stress resistance and inhibit disease by increasing the bioactive components of the plant ( Zhang et al, 2020 ). Furthermore, the plant growth promoting fungi (PGPR) have been widely used to prevent and control heavy metal pollution due to its ability to promote plant growth and induce host resistance ( Geetha et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the LDA results showed that three beneficial taxa belonging to Ascomycota ( Archaeorhizomyces , Dactylella , and Helotiales ) were only abundant in the low altitude group. Archaeorhizomyces and Dactylella are widespread fungal taxa in many soil environments and can elevate plant bioactive compositions, promote stress tolerance, and alleviate the occurrence of plant diseases ( 38 , 39 ). The genus of Helotiales comprises a large number of ectomycorrhizal fungi and plays a pivotal role in providing soil N/P to their hosts ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%